All this means is (f(x)) + (g(x))
2x-1+ x^2-3x-2=
=== x^2 - x -3
Hello there, you can proceed with the multiplication of these factors using the FOIL method (which stands for first, outer, inner and last) multiply I assume that by descending order, you mean by decreasing power. If it were so, the answer is 6(x^3)12(x^2)-16(x^2)32x-27x+72.
Put into slope intercept form, y=mx+b where m=slope
p=-2q+6
slope is -2
subsitute values for q and get values for p
q=0, p=6
(q,p)
(0,6)
(1,4)
p=q+4
slope is 1
subsitutte
q=0,p=4
(q,p)
(0,4)
(1,5)
below are the graphs
Answer:
What is your specific question regarding Pq?
Step-by-step explanation: